Analisis Tax Planning PPh Badan melalui Perbandingan Gross-Up Method dan Net Method serta Deductible dan Non-Deductible Expenses guna Meminimalkan Pembayaran Pajak Penghasilan (PPh) Badan pada PT XYZ - Nicholas, Irvin (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2024)
This study examines corporate income tax planning at PT XYZ by comparing the Gross-Up Method and the Net Method and by analyzing deductible and non-deductible expenses. The study employs a descriptive qualitative approach using secondary data consisting of PT XYZ’s 2022 financial statements and employee income records. Data were collected through documentation and analyzed with reference to applicable Indonesian tax regulations. The results indicate that the Gross-Up Method is more effective than the Net Method because the tax allowance provided to employees can be treated as a deductible expense in the company’s fiscal financial statements. The study also finds that PT XYZ has not implemented tax planning effectively because its strategy remains limited and several expenses still require fiscal correction. After applying tax-planning strategies to deductible and non-deductible expenses, the company’s fiscal net income decreased from Rp2,412,156,348 to Rp2,339,379,370, while corporate income tax payable decreased from Rp431,292,780 to Rp418,280,273. Thus, the proposed tax-planning strategies generated corporate income tax savings of Rp13,012,507.